Model Kurikulum Pendidikan Meningkatkan Etos Kerja Muslim di Lingkungan Kedinasan - Obay Sobari; Ulil Amri Syafri; Budi Handrianto (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2020)
Problems in this research is how a work ethic muslim Who actually have a wonderful concept of good from Al Qur'an and As Sunnah. But there plenty of found a muslim who worked manner and the force that far from islamic values, especially with ethical or work ethos ? Therefor, This research aims to to apply one model curriculum to increase work ethic muslim. This research study using a library reasearch method, that traits of descriptive qualitative with the collection of primary data through of reference main book While secondary data it obtained through interviews to officials, section head, and several employees of Office of customs and excise Bogor. The research results show that The application of the concept of education curriculum to improve muslim work ethos in the government office Need to continue to get more attention, Both in the concept and application and supervision also.